Analysis of The Effect of Variations in Smaw Welding Current on Indications of Surface Defects Using The Penetrant Test (PT) and Magnetic Particle Test (MT) on ASTM A106 GR. B Pipes Based on Asme B31.3 Acceptance Criteria - Ugih Sugiarto; Adri Fato (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Shielded Metal Arc Welding (SMAW) is one of the most widely used metal joining processes in the piping industry because it is capable of producing weld joints with good quality and mechanical strength. One of the welding parameters that significantly affects weld quality is the welding current. An inappropriate current setting may increase the occurrence of surface discontinuities, which can reduce the quality of the welded joint. This study aimed to analyze the effect of SMAW welding current variations on surface discontinuity indications in ASTM A106 Grade B pipe using the Penetrant Test (PT) and Magnetic Particle Test (MT) methods based on the Acceptance Criteria of ASME B31.3. The research was conducted using an experimental method on ASTM A106 Grade B pipe welded with an E7018 electrode of 3.2 mm diameter in the 1G welding position. The welding current variations applied were 46 A, 65 A, 88 A, 115 A, 160 A, and 210 A. Each specimen was initially examined through Visual Inspection, followed by Penetrant Test (PT) and Magnetic Particle Test (MT) to identify surface discontinuity indications. The inspection results were subsequently evaluated according to the Acceptance Criteria of ASME B31.3. The results showed that variations in welding current affected the surface quality of the welded joints. At welding currents of 46 A and 65 A, porosity and incomplete fill indications were still observed, while undercut indications were identified at 160 A and 210 A. In contrast, the specimens welded at 88 A and 115 A showed no discontinuity indications exceeding the acceptance limits and were therefore classified as acceptable. Based on the evaluation in accordance with the Acceptance Criteria of ASME B31.3, it can be concluded that the welding current range of 88 A to 115 A produced the best weld surface quality under the conditions of this study.